Create A Safe Environment by First Aid Demonstrating Based On Family Health In Banjarsari Village, Trucuk District, Bojonegoro Regency - Abidin, Ahmad Zainal; Julianto, Errix Kristian (Jurnal Humanis ( Jurnal Pengabdian Masyarakat ISTeK ICsada Bojonegoro), 2024)
Health in society is a vital need in the development and development of the nation's health, so it is very important to be able to create and foster healthy lifestyles in society. Health is not limited to aspects of disease threat conditions alone, but also environmental threat conditions and also other aspects that can affect health. Some things that often have an influence on health conditions are human error conditions (such as choking and so on), cardiac arrest, trauma/accidents, bite attacks from wild and venomous animals. This is also an aspect of health that must be well known by every community, both in terms of knowledge, causes, prevention and at least knowing how to deal with it, so that with adequate community capacity in responding to problems that occur in the surrounding environment, there will be a great opportunity to be able to create environmental conditions. safe, healthy and prosperous based on individual, family and community awareness. The aim of implementing this community service is to improve the level of community health: creating a safe, healthy and prosperous environment by providing assistance to families. Assistance for assisted families is carried out in Banjarsari village, Bojonegoro subdistrict, Bojonegoro district. The families who will be accompanied are 11 assisted families. The implementation of mentoring for assisted families will be carried out based on the POA (Planning Of Action) that has been created. Lecturers and students will visit the target families according to the previously agreed time contract. The results of this research were that the status of the assisted families before being given the program had an average PHBS of 73.8% in the pre-healthy category with an average independence of 75.33% in the independent category. Meanwhile, after being given the health program, the average PHBS was 79.98% in the pre-healthy category with an average independence of 82.17% in the very independent category and as a result of this service the knowledge possessed by the family before being given the first aid program was average. -The average is 58.7%, the majority is in the poor category, while the results after being given the program are knowledge acceptance, namely 76.18% in the medium category. We are making this effort to foster community health by stimulating families as the pillars of health so that they are able to create a safe environment together and be more aware of health, safety and security together. So that a more effective and productive environment will develop in carrying out all forms of activities and work.